‘Middle-class’ Africans in Australia: choosing Hillsong as a global home - Rocha, Cristina (Culture and religion, 2021)
Much of the literature on Pentecostal-charismatic Christianity (Pc/C) and African diasporas in the Global North has focused upon African-Majority or -Initiated churches that are either branches of African churches or were created in the diaspora. This focus often frames the appeal of Pc/C to African migrants in terms of: a) its emphasis upon the ‘Prosperity Gospel’ offering a path not only to salvation, but also to earthly riches; b) its opportunities for achieving status among church hierarchies, which is attractive to socially marginalised groups, and; c) the practical assistance it provides to support settlement. However, African diasporas have diverse histories of migration, and settlement experiences. This article considers the appeal of Pc/C to a group of professional African migrants in Australia, who self-identify as ‘middle-class’. It argues that professional African migrants have consciously favoured the Australian megachurch Hillsong over Australia’s African-Initiated churches. They have done so in pursuit of a process of an imagined class-mobility, and as a result, their choice of church can be understood as largely strategic.